Enhancing Purchase Intentions in Online Shopping: A Case Study on Live Streaming, Credibility Of Celebrity Endorsement, and Perceived Benefits - Isnaini Dwi Aprilia; Rita Ambarwati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Shopping face-to-face or live streaming has become a form of onlineshop that entrepreneurs use to demonstrate the usefulness of the products being sold, showcase products from various angles and perspectives, respond directly to consumers and carry out activities that can attract consumer buying intentions to make purchases while watching live streaming. The purpose of this study is to determine the impact between live streaming variables (X1), Credibility Of Celebrity Endorsement (X2), Perceived Benefits (X3) on Purchase Intention (Y). This research was conducted on the marketplace application. This study uses a survey method where primary data is obtained from questionnaire data. The sample was those who had shopped on live streaming which was taken randomly (random sampling) as many as 127 respondents. The data analysis method uses SEMPLS 3.0. The results prove that live streaming has a positive and significant impact on purchase intentions. Credibility of Celebrity Endorsement has a positive and significant influence on purchase intentions. Perceived Benefit has a positive and significant influence on purchase intentions.